Development of Learning Outcomes Assessment Instruments on Excretory System Materials - Hajrazul Pitri; Ismul Huda; Hasanuddin Hasanuddin; Cut Narmaliah; Wiwit Artika; Rizki Zulia Ningsih; Syamsulrizal Syamsulrizal; Abu Bakar (Proceedings of AICS - Social Sciences, 2021)
This study aims to develop a learning outcome assessment instrument to determine a tool set's validity, reliability, discrimination power, and level of difficulty. The type of research used is developmental research. The subject of this research is the instrument for assessing the learning outcomes of the excretory system material. The data obtained will be analyzed for validity, reliability, discrimination power, and the level of difficulty of each instrument. The average value of the data analysis test shows that the tested data has high validity, a sufficient level of reliability, moderate discrimination power and a sufficient level of difficulty. The results of data testing carried out in class XII IPA at SMAN 12 Banda Aceh can be stated that the excretory system learning outcomes instrument is feasible to be developed and used in assessing learning outcomes to students.Keywords: instrument, reliability, validity